Effects of biochar amendment and arbuscular mycorrhizal fungi inoculation on availability of soil phosphorus and growth of maize - A E Mau; S R Utami (Brawijaya University, 2014)
A glasshouse experiment was conducted to study the interactive effects of biochar amendment and arbuscular mycorrhizal fungi (AMF) inoculation on phosphorus uptake by maize (Zea mayze L.) grown on a calcareous soil of Kupang, East Nusa Tenggara. The biochar was made of cow dung. Twelve treatment combinations (three biochars levels of 0, 5 and 7.5 g/kg of soil, and four AMF inoculation levels of 0, 5, 10 and 15 spores / kg of soil) were arranged in a completely randomized block design with three replicates. Results of the study showed that at 8 weeks after transplanting, the biochar and mycorrhizal treatments increased the availability soil phosphorus and phosphorus uptake by maize. Application 4.5 and 7.5 g biochar/kg of soil combined with inoculation of 10-15 AMF spores / kg of soil provided to high value of phosphorus uptake by maize. Application of biochar alone, however, did not significantly improve maize growth and phosphorus uptake by maize.